2005
DOI: 10.1080/10253860500160320
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners in Paradise: Subcultural Resistance to the Marketization of Tattooing

Abstract: This study explores the increasingly popular use of brand symbols as imagery for tattooing. Through interviews with tattoo artists and netnographic research in tattoo communities, we capture a perceived boundary between the sacred, non-commercial sphere of tattooing and the profane, profit maximizing sphere of the commercial world. In the tattoo subculture, brands are generally considered inappropriate for tattooing. Nevertheless, the tattoo artists more or less willingly accept the role of service providers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Tattoos have been extensively researched from the point of view of employee selection (Bekhor et al, 1995;Swanger, 2006;Timming, 2015;Timming et al, 2015) and relationship marketing (Bengtsson et al, 2005;Totten et al, 2009;Patterson and Schroeder, 2010;Dean, 2010Dean, , 2011Arndt and Glassman, 2012;Doleac and Stein, 2013;Bjerrisgaard et al, 2013), but this study marks the first time that the two fields have been brought together into one analysis. Drawing from the literature on aesthetic and branded labour (Warhurst et al, 2000;Witz et al, 2003;Pettinger, 2004;Entwistle and Wissinger, 2006;Warhurst and Nickson, 2007), this paper argues that visible tattoos on front-line service employees can not only promote relationship building with tattooed customers, but also, under a unique set of circumstances, concomitantly improve visibly tattooed job applicants' employability.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tattoos have been extensively researched from the point of view of employee selection (Bekhor et al, 1995;Swanger, 2006;Timming, 2015;Timming et al, 2015) and relationship marketing (Bengtsson et al, 2005;Totten et al, 2009;Patterson and Schroeder, 2010;Dean, 2010Dean, , 2011Arndt and Glassman, 2012;Doleac and Stein, 2013;Bjerrisgaard et al, 2013), but this study marks the first time that the two fields have been brought together into one analysis. Drawing from the literature on aesthetic and branded labour (Warhurst et al, 2000;Witz et al, 2003;Pettinger, 2004;Entwistle and Wissinger, 2006;Warhurst and Nickson, 2007), this paper argues that visible tattoos on front-line service employees can not only promote relationship building with tattooed customers, but also, under a unique set of circumstances, concomitantly improve visibly tattooed job applicants' employability.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…On the other hand, Dean (2010Dean ( , 2011 and Arndt and Glassman (2012) researched consumers' perceptions of tattooed employees, concluding that body art contributes to a largely negative service experience. Bengtsson et al (2005) show how corporate brand tattoos (see also Orend and Gagné, 2009) are doubly despised by both the tattoo subculture and mainstream culture. Doleac and Stein (2013) found that consumers are significantly less likely to purchase products from employees with visible tattoos.…”
Section: Introductionmentioning
confidence: 99%
“…A biker participates, imitates, and commits to the subculture by adopting the similar material appearance of the Harley Davidson bikers' community. Similarly, a modification of the body using plastic surgery or tattooing is strongly driven by the desire to project a certain image to others (Bengtsson, Ostberg, and Kjeldgaard 2005;Schouten 1991). It is an act of self-expression, modifying the body enables consumers to engage and be accepted in a particular social world or subculture.…”
Section: Separationmentioning
confidence: 98%
“…In another study (Goulding et al, 2004) delved into the client/provider relationship. Kjeldgaard and Bengtsson (2004) described tattooing as the consumption of fashion, while Bengtsson et al (2005) examined the phenomenon of brand tattooing. A postmodern account of the consumption of tattoos and simulated self and identity is given by Velliquette et al (1998).…”
Section: Tattoos -Now and Thenmentioning
confidence: 99%